Kendo UI Cookbook : over 50 recipes to help you rapidly build rich and dynamic user interfaces for web and mobile platforms - Ganatra, Sagar (Community experience distilled., 2014)
This book is an easy-to-follow guide full of hands-on examples that allows you to learn and build visually compelling web applications using the Kendo UI library. This book will do wonders for web developers having knowledge of HTML and Javascript and want to polish their skills in building applications using the Kendo UI library.